Satu Suara untuk Perubahan: Sebuah Projek untuk Mengajak Peserta Didik Menjadi Warganegara yang Baik dan Cerdas - Chania Dwi Chusnul Analisah; Ana Agustin Purwaningsih (eductum: Jurnal Literasi Pendidikan, 2023)
The conflicts regarding election results, decreasing public participation in political activities, eroding critical thinking, misinterpretation of freedom of speech, uncontrollable feelings of insecurity due to a lack of self-confidence in facing competition, stereotypes and cynicism corroding respect for diversity and differences are evidence that society has not fully realized its potential. The community has not been able to internalize the noble values of respecting differences, equality, freedom, ethics, and consensus contained in Pancasila. This phenomenon raises the question of how to teach these values to children. What kind of school can accommodate various needs to teach these values? What kind of education is needed? Should education involve more philosophical elements? More media literacy? More elements of citizenship? Or more historical elements? This research aims to describe the implementation of the Strengthening Student Pancasila Profile (P5) project with the theme "Voice of Democracy" and the topic "One Voice for Change" as part of the implementation of the Free Curriculum. The research method used is qualitative description. This study involves students from UPT Public Junior High School 5 in Mojokerto, in the seventh and eighth grades. The sources of research data come from interviews, observations, and documentary studies. The results of the research show that the implementation of P5 is able to increase active participation of students in expressing their voices as a manifestation of good democratic practices in daily life. It is also able to shape the character profile of Pancasila students; morality towards the state, mutual cooperation, and critical thinking.